Phenotypes, Predictors and Outcome of Hypertension in the Inpatient Setting - Mohammad Mujtaba Khokhar, Zafar Aleem Suchal (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
Background: Hypertension (HTN) is a leading preventable cause of cardiovascular disease and mortality globally. It poses a massive burden of disease in Pakistan, with the National Diabetes Survey of Pakistan 2016-2017 conducted on 10,834 participants nationwide, reporting an overall age-adjusted weighted prevalence of 46.2%. Yet, data on its management in hospitalized non-cardiac patients remains underexplored. Understanding the inpatient non-cardiac population patterns of hypertension management is hence crucial for enhancing outcomes and patient management protocols. Objectives: This study thus aims to evaluate the prevalence, treatment patterns, and outcomes of hypertension in the non-cardiac inpatient population, with a focus on complications, medication adherence, and discharge planning. Methods: A cross-sectional study was conducted over five months (November 2024 to March 2025) at Shalamar Hospital, Lahore. Adult patients (≥18 years) admitted with known or newly diagnosed hypertension were enrolled. Data on demographics, clinical characteristics, inpatient BP trends, treatment modalities, and outcomes were collected through structured questionnaires and medical record review. Statistical analyses were performed using SPSS v27. Results: Among 151 hypertensive inpatients (mean age 58.2 ± 12.8 years; 68.9% female), 77.5% had a prior HTN diagnosis, and 67.5% reported treatment adherence pre-admission. Diabetes (81.9%) and chronic kidney disease (13.8%) were the most common comorbidities. Hypertension was actively managed in 78.2% of patients, yet 18.5% received no treatment during admission. Oral antihypertensives were used in 72.1%, with 37.7% receiving monotherapy. Complications included hypertensive emergencies (5.3%), renal failure (8.0%), and myocardial infarction (2.6%). Only 29.1% had documented follow-up plans at discharge. Poor BP control correlated with renal dysfunction, inadequate medication use, and lack of specialist referrals (p<0.05). Conclusion: Despite a high prevalence of hypertension among inpatients in Pakistan, gaps exist in the management of such patients, such as improper treatment, less robust follow-up planning, and high rates of complications. These findings urge the need for apt utilization and implementation of standardized inpatient hypertension management protocols in Pakistan to improve patient outcomes and decrease the healthcare burden.